Highlights of AUTC's learning outcomes and curriculum development in law report. - Johnstone, Richard; Vignaendra, Sumitra (Australian Learning & Teaching Council, 2009)
The 500-page Learning Outcomes and Curriculum Development in Law report painted an excellent picture of the Australian legal education landscape as it existed at the beginning of 2003. It mapped the significant changes that had taken place in legal education since the seminal Pearce Report of 1987. However, the dissemination methods used by the AUTC were not sufficient to allow this information to reach Australian legal academics in a meaningful way. Although things have developed in the last six years, much of the information, especially as it discloses trends, remains useful and relevant, and the work of the current ALTC/CALD Law project builds from it. This resource is designed to provide Australian legal academics with an accessible introduction to the report. The challenges posed by the report include: to promote incremental and coordinated approaches to curriculum development; better evaluation of effectiveness of teaching strategies; sharing of effective teaching strategies, policies and practices; and most of all; uniform promotion of scholarly approaches to teaching and curriculum development. The latter part of this resource provides case studies of 2009 innovative directions.